South Park: (des)construção iconoclasta das celebridades - Oliveira, Érico Fernando de (2012)
The reason of this research is studying the contemporary and social construction of the celebrities as well as the role that it exerts at the mediatic civilization. Therefore we focused on the American TV show South Park, an animation that is dedicated at caricature them. We worked with the hypothesis that the idol is a simulacrum that doesn t resist to humor desecrate. In order to do that we adopted as the main investigative theorist reference the concepts of dispositive and profanation from Giorgio Agamben s philosophy, to whom the caricature present on the cartoons reveals the human and ordinary character of the idols, taking off the phantasy veil which sacralizes it. But we also mobilize as other conceptual operators the lacanian real , once that by definition he doesn´t let himself lose from the imaginary as well as the symbolic and cynical subject notion, as developed by Slavoj i ek, which takes us to elaborate another hypothesis, the one that the engaging at the modalization defiler of the show might not occur because of the cynical reception of its audience. The corpus selected to analysis constitutes of 71 episodes of 22 minutes duration selected among more than 200 of the previously mentioned TV show, aired between 1997 and 2011, as well as the feature film South Park: bigger, better and uncut (1999). The selection was made mostly based on the purpose of what we intend to show